Risk of HIV transmission from patients on antiretroviral therapy: A position statement from the Public Health Agency of Sweden and the Swedish Reference Group for Antiviral Therapy. (October 2014) - Albert, Jan; Berglund, Torsten; Gisslén, Magnus; Gröön, Peter; Sönnerborg, Anders; Tegnell, Anders; Alexandersson, Anders; Berggren, Ingela; Blaxhult, Anders; Brytting, Maria; Carlander, Christina; Carlson, Johan; et al.
Abstract The modern medical treatment of HIV with antiretroviral therapy (ART) has drastically reduced the morbidity and mortality in patients infected with this virus. ART has also been shown to reduce the transmission risk from individual patients as well as the spread of the infection at the population level. This position statement from the Public Health Agency of Sweden and the Swedish Reference Group for Antiviral Therapy is based on a workshop organized in the fall of 2012. It summarizes the latest research and knowledge on the risk of HIV transmission from patients on ART, with a focus on the risk of sexual transmission. The risk of transmission via shared injection equipment among intravenous drug users is also examined, as is the risk of mother-to-child transmission. Based on current knowledge, the risk of transmission through vaginal or anal intercourse involving the use of a condom has been judged to be minimal, provided that the person infected with HIV fulfils the criteria for effective ART. This probably also applies to unprotected intercourse, provided that no other sexually transmitted infections are present, although it is not currently possible to fully support this conclusion with direct scientific evidence. ART is judged to markedly reduce the risk of blood-borne transmission between people who share injection equipment. Finally, the risk of transmission from mother to child is very low, provided that ART is started well in advance of delivery.